ANALYSIS OF THE FACTORS AFFECTING THE THERMOPHYSICAL STATE OF A SMALL-CALIBER ARTILLERY BARREL (Web of Teachers: Inderscience Research, 2025)
This article analyzes the factors affecting the thermophysical state of the barrel of small-caliber aviation artillery weapons (AAW), and provides the main achievements and shortcomings of factors affecting heat resistance, and the prospects for their development indicated.